2022
DOI: 10.1177/17534666221092993
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics in adult patients with somatic cough syndrome

Abstract: Objective: The data in regard of the clinical characteristics and diagnosis of somatic cough syndrome in adults were limited. The aim of this study was to fill that gap. Methods: This was a retrospective analysis of patients with somatic cough syndrome. We described clinical characteristics of adult patients with somatic cough syndrome. Results: Twenty-three somatic cough syndrome patients were identified in 543 adult patients with chronic cough. Psychiatric disorder of these patients was identified as anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Studies have shown that although 54% of psychogenic cough patients who are awake at night have the most serious cough symptoms, 93% of the coughing disappears completely when sleeping, 24 and somatic cough syndrome patients had a lower proportion of nocturnal cough. 6 Our study also showed that although PCC patients had persistent night cough symptoms, the symptoms were milder than the other two groups, which suggests that cough symptoms in this group may be more psychologically related. In addition, in the SCC group, gastroesophageal reflux-induced chronic cough (GERC) was the most common etiology.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Studies have shown that although 54% of psychogenic cough patients who are awake at night have the most serious cough symptoms, 93% of the coughing disappears completely when sleeping, 24 and somatic cough syndrome patients had a lower proportion of nocturnal cough. 6 Our study also showed that although PCC patients had persistent night cough symptoms, the symptoms were milder than the other two groups, which suggests that cough symptoms in this group may be more psychologically related. In addition, in the SCC group, gastroesophageal reflux-induced chronic cough (GERC) was the most common etiology.…”
Section: Discussionsupporting
confidence: 58%
“…According to some studies, the median duration of psychogenic cough in children is 3 months, 24 while a retrospective study used the term ‘somatic cough syndrome’ with a median course of 48 months in adults. 6 In this study, the median duration of PCC was 6 months, which was shorter than the SCC group. This may be because PCC patients have a basis of psychological disease before the occurrence of cough, as well as sensitivity to their cough symptoms.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Distinguishing between somatic chronic cough and non-somatic chronic cough can be challenging [ 5 ], as patients with chronic cough are more prone to experiencing psychological disorders such as anxiety and depression, which can, in turn, exacerbate the coughing. While it is commonly believed that somatic chronic cough tends to occur more frequently when patients are awake and less frequently during sleep, the presence of accompanying physiological conditions such as gastroesophageal reflux, postnasal drip, bronchitis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…While it is commonly believed that somatic chronic cough tends to occur more frequently when patients are awake and less frequently during sleep, the presence of accompanying physiological conditions such as gastroesophageal reflux, postnasal drip, bronchitis, etc. can still result in pronounced nocturnal coughing [ 5 ]. The presence or absence of nocturnal cough cannot be used as the sole basis for diagnosis; somatic cough syndrome can only be diagnosed when a patient meets the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criteria [ 3 , 5 ].…”
Section: Discussionmentioning
confidence: 99%